2020
DOI: 10.3390/ijms21218280
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and the Oviduct Function

Abstract: In mammals, the oviduct (or the Fallopian tube in humans) can be divided into the infundibulum (responsible for oocyte pick-up), ampulla (site of fertilization), isthmus (where preimplantation embryos develop), and uterotubal junction (where embryos transit to the uterus). The oviductal fluid, as well as extracellular vesicles produced from the oviduct epithelial cells, referred to as oEVs, have been shown to improve the fertilization process, prevent polyspermy, and aid in embryo development. oEVs contain mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 92 publications
0
38
0
Order By: Relevance
“…In the uterus, stromal‐derived IGF1 stimulates epithelial cell proliferation through a paracrine mechanism 11 . It was previously shown that secreted factors present in the extracellular vesicles can diffuse through the zona pellucida and bind to the plasma membrane of bovine preimplantation embryos 73 . Therefore, it is possible that in the mouse oviduct, secreted IGF1 can be diffused in a similar fashion as in the uterus through epithelial cells and promote embryo development in the oviductal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…In the uterus, stromal‐derived IGF1 stimulates epithelial cell proliferation through a paracrine mechanism 11 . It was previously shown that secreted factors present in the extracellular vesicles can diffuse through the zona pellucida and bind to the plasma membrane of bovine preimplantation embryos 73 . Therefore, it is possible that in the mouse oviduct, secreted IGF1 can be diffused in a similar fashion as in the uterus through epithelial cells and promote embryo development in the oviductal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to alter the fertilization conditions to improve monospermy rates. These efforts have included altering the concentration of sperm while varying the duration of exposure between the sperm and oocytes, adding follicular fluid [33] or substances found in oviductal fluid, such as deleted in malignant brain tumors 1 (DMBT1) [34], oviductal glycoprotein 1 (OVGP1) [35], secreted phosphoprotein 1 (SPP1) [36], or plasminogen [37,38], as well as trying to recreate the oviductal environment by adding oviductal fluid [39,40] or oviductal extracellular vesicles [41], among other things [42].…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
“…Also, when it comes to the proper communication and regulation between gametes/embryos and the fallopian tube, extracellular vesicles also paly important role in the multi-steps process. For example, proteins including endothelial nitric oxide synthase (eNOS), PMCA1 and PMCA4 can be delivered to sperm by extracellular vesicles via a fusogenic mechanism, and contributing to the sperm viability (37)(38)(39).…”
Section: Female Fertility Healthy Physiology and Extracellular Vesiclesmentioning
confidence: 99%